Microphone arrays application in three-dimensional sound source localisation. (1st January 2012) - Kornatowski, Eugeniusz
This article describes the problems of use of spatial microphone arrays in sound source location. Questions concerning modelling of planar (2-D) and spatial (3-D) directional characteristics of microphone arrays are discussed. Typical algorithms used in SSL system are also described. The paper describes options to use a single point surround microphone to determine a direction of the sound source localisation. A 'soundfield' microphone with four transducers (capsules) characterised by cardioid directivity pattern. A unique mechanical design of the transducer results in its omnidirectional directivity pattern. The microphone enables 3-D sound acquisition in so called A-format. Upon further processing of signal it is possible to determine, e.g., a direction of a sound source within space. The conducted experiments prove that a simple calculation algorithm is in particular feasible for a real time operation, and application of the soundfield microphone significantly simplifies mechanical design of the SSL system.